Aspectos estruturais, farmacológicos e biológicos de fucanas da alga marrom sargassum vulgare - Dore, Celina Maria Pinto Guerra (2012)
The present study examines the chemical composition and their effects on free radicals, inflammation, angiogenesis, coagulation, VEGF effects and cellular proliferation of a polysaccharides from alga Sargassum vulgare. The sulfated polysaccharide was extracted from brown seaweed by proteolysis with enzymes maxataze. The presence of proteins and sugars were observed in crude polysaccharides. Fractionation of this crude extract was made with growing concentration of acetone (0.3-1.5 v) and produced four groups of polysaccharides. Anionic polysaccharides from brown seaweed Sargassum vulgare, SV1and PSV1 were fractionated (SV1) and purified (PSV1), and displayed with high total sugars and sulfate content and very low level of protein. This fucan SV1 contains low levels of protein and high carbohydrate and sulfate content. This polysaccharides prolonged activated partial thromboplastin time (aPTT) at 50 μg (>240 s). SV1 was found to have no effect on prothrombin time (PT), corresponding to the extrinsic pathway of coagulation. SV1 exhibits high antithrombotic action in vivo, with a concentration ten times higher than heparin. Polysaccharides from S. vulgare promoted direct inhibition enzymatic activity of thrombin and stimulated enzymatic activity of FXa. SV1 showed optimal inhibitory activity of thrombin (50.2±0.28%) at a concentration of 25 μg/mL. Its antioxidant action on scavenging radicals by DPPH was (22%), indicating the polymer has no cytotoxic action (hemolytic) on ABO and Rh blood types in different erythrocyte groups and displays strong anti-inflammatory action on all concentrations tested in the carrageenan-induced paw edema model, demonstrated by reduced edema and cellular infiltration. Angiogenesis is a dynamic process of proliferation and differentiation. It requires endothelial proliferation, migration, and tube formation. In this context, endothelial cells are a preferred target for several studies and therapies. The antiangiogenic efficacy of polysaccharides was examined in vivo in the chick chorioallantoic membrane (CAM) model by using fertilized eggs. Decreases in the density of the capillaries were assessed and scored. The results showed that SV1 and PSV1 have an inhibitory effect on angiogenesis. These results were also confirmed by inhibition tubulogenesis in rabbit aorta endothelial cell (RAEC) in matrigel. These compounds were assessed in Apoptosis assay (Annexin V - FITC / PI) and cell viability by MTT assay of RAEC. These polysaccharides do not affect the viability and do not have apoptotic or necrotic action. RAEC cell when incubated with SV1 and PSV1showed inhibition of VEGF secretion, observed when compounds were incubated at 25, 50 and 100 μg/μL. The VEGF secretion with the RAEC cell line for 24 h, was more effective for PSV1 at 50 μg/μL(71.4%) than SV1 100 μg/μL (75.9%). SV1 and PSV1 had an antiproliferative action (47%) against tumor cell line HeLa. Our results indicate that these sulfated polysaccharides have antiangiogenic and antitumoral actions